Enhancing collocation noticing and intake through textual enhancement technique among low-proficiency ESL learners - Masturah, Sabri (2024)
This study examines the effects of Textual Enhancement (TE) on students' noticing and acquisition of collocations using a mixed-methods design, combining quasiexperiment with focus group interviews. This study investigates the influence of textual enhancement (TE) on the noticing and acquisition of collocation knowledge, with motivational factors as a contributing variable. It also explores the “spillover” effect, assessing whether the impact of partially enhanced collocations extends to unenhanced ones. Additionally, it evaluates the effectiveness enhancement and their lasting impact on low-proficiency learners at a public university in northern Malaysia. Participants are divided into three groups, each reading passages with: (a) fully enhanced collocations (highlighted and bolded), (b) partially enhanced collocations (either highlighted or bolded), and (c) non-enhanced collocations. The mixed-methods design includes a quasi-experiment and focus group interviews, involving 108 participants from three intact classes to ensure consistency across proficiency levels. Each class was randomly assigned to either treatment or control group conditions through draw lots. Focus group interviews were conducted among 12 participants representing high, medium, and low scores. TE technique significantly enhanced students' ability to identify and acquire short-term collocations among low-proficiency L2 learners but had no significant long-term effects. Qualitative findings emphasize the need for clear instruction, regular practice, and interactive methods to support collocation learning. This study contributes to understanding the role of TE in both short and long-term language acquisition, as well as the need for effective pedagogical strategies for teaching collocations in the ESL context. It offers refined and flexible pedagogical guidelines tailored to low-proficiency learners, promoting collocation recognition and retention, as well as learner autonomy through collaborative tasks, and explicit teaching